Case studies: electronic mail records management practices of academic institution in northern region Malayasia / Siti Khairunnisa Sheikh Abdul Mutalib ... [et al.] - Sheikh Abdul Mutalib, Siti Khairunnisa; Mohammed Ghazali, Asmadi; Abdul Rahman, Abdul Latif (2015)
The aim of this study is to identify the electronic mail records management in selected organization in northern region Malaysia. Electronic mail or also known as e-mail is one of the types of electronic records which regularly used in business or personal transactions. E-mail records management need to be organized accordingly in the selected organization so it can increase productivity and efficiency. The main purpose of the study is to assess the practices among the organization which use an e-mail as their electronic records and business process. The study is to identify the existence of a proper record keeping system in managing the organization . A framework was developed to assist selected organization in managing their e-mail records more effectively. The researcher gathered the data for the research question from interview session with selected respondents regarding what are the best practices of managing e-mail as record in academic institutions, northern region, Malaysia in accordance with National Archive Act 2003 and MAMPU policy, and how the organization keeping and storing the e-mail records. The results from the study, will come out with the e-mail records management practices framework and flow following the records management guideline and record keeping system . The findings from the study will help the organization to manage the email and service effectively and efficiently